Leistungsklassen und Geschlechtertests Die heteronormative Logik des Sports - Heckemeyer, Karolin (Transcript-Verlag, 2018)
Assumption about physical performance and gender are closely interwoven in sports - how are they reproduced and how are they legitimized?
Keywords: Feminism and sports; Gender studies, gender groups; Heterosexism; Professional sports; Queer theory; Social Science; Sports; Women athletes; Sports -- Social aspects; Sports -- Sociological aspects; Geschlechterverhältnis; Leistungssport; Weiblichkeit; Körperbild; Frauensport; Soziales Feld; Geschlechterstereotyp; Geschlechtersoziologie; Electronic books; Academic theses; Hochschulschrift